Prosecutions for violent offences in selected English, Australian and New Zealand Petty Sessions' Courts, 1880-1914 - Godfrey, Barry S. (UK Data Service, 2002)
Violent crime has provided a major focus for the study of inter-personal relationships and a range of related research areas in the fields of history, criminology and sociology. However, somewhat surprisingly, the extent, character and 'meanings' of violence in the late-nineteenth and early-twentieth centuries have been relatively ignored. Yet during the period 1880 to 1920 prosecuted violent offences in magistrates' courts fell by over 75 per cent to their lowest ever level. Such statistics immediately provoke questions for social scientists. Can we accept that there was a seismic shift in behavioural norms across society? Alternatively, did governmental administrative/economic expediencies produce a 'mirage' of declining violence? Both theories have been advanced for the decline in homicide rates since the 18th century. This project uses a range of sources/methods to examine changes in real incidence and prosecutorial strategies, and, through study of cities in Australia and New Zealand, steps beyond English socio-cultural contexts to complete a truly comparative project which fully explores violent crime in the fin de siecle period.